2019
DOI: 10.1002/jssc.201900248
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of new antiepileptic compounds by combining chromatography on the phosphatidylcholine biomimetic stationary phase and differential scanning calorimetry

Abstract: Liquid chromatography coupled to spectrophotometric detection of new antiepileptic compounds, 1,2,4‐triazole‐3‐thione derivatives, on immobilized artificial membrane phosphatidylcholine is reported. The curves representing the relationship between ln k versus 1/T generated under isocratic conditions by the use of methanol and acetonitrile‐containing eluent systems have been constructed in order to determine the thermodynamic parameters: the enthalpies, entropies and the relative free energies. The hydrocarbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This HPLC column has been designed for the prediction of drug-membrane interactions. There is evidence that the retention measured on this column correlates to traditional in-vitro methods such as Caco-2 cell line cultures, intestinal tissue, or liposome assays [34,35,36]. However, it has been previously discovered that inorganic anions are also able to retain on a phospholipid monolayer by Hu et al [37].…”
Section: Introductionmentioning
confidence: 99%
“…This HPLC column has been designed for the prediction of drug-membrane interactions. There is evidence that the retention measured on this column correlates to traditional in-vitro methods such as Caco-2 cell line cultures, intestinal tissue, or liposome assays [34,35,36]. However, it has been previously discovered that inorganic anions are also able to retain on a phospholipid monolayer by Hu et al [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies showed that the membrane partition measured by IAM chromatography could provide a more reliable assessment, especially when the compounds are charged. The thermodynamic aspects of the binding of new antiepileptic compounds to C‐18 and IAM stationary phases have been investigated and compared using differential scanning calorimetry 53 . It was found that heteroatoms such as oxygen and sulphur in the triazole ring were responsible for the selectivity differences in the IAM interactions supported by molecular dynamics calculations.…”
Section: New Applications and Modelsmentioning
confidence: 99%
“…Therefore, the investigated 1,2,4-triazole derivatives (named TPR) seem to be an interesting group of antiepileptic drug candidates. In our previous papers [15,42], we examined these compounds on the cholesterol-based stationary phase, and the commercially available phosphatidylcholine biomimetic stationary phase [42]. Molecular dynamics simulations revealed the selective preferences of the phosphatidylcholine with respect to the compounds with either ether or sulfide moieties.…”
Section: Scheme 1 Schematic Representations Of Stationary Phases (A)mentioning
confidence: 99%
“…The details of the anticonvulsant activity evaluation procedure and subsequent results are partially described in our previous works [15,37,42]. The anticonvulsant activity of the investigated compounds was measured in mice maximal electroshock (MES)-induced seizure model of epilepsy.…”
Section: Evaluation Of Anticonvulsant Activitymentioning
confidence: 99%